Bioinorganic chemistry : (Wiley-Interscience, 2007)
Bioinorganic chemistry: a short course, second edition provides the fundamentals of inorganic chemistry and biochemistry relevant to understanding bioinorganic topics. Rather than striving to provide a broad overview of the whole, rapidly expanding field, this resource provides essential background material, followed by detailed information on selected topics. The goal is to give readers the background, tools, and skills to research and study bioinorganic topics of special interest to them.